Implementation of the Local Wisdom-Based Education Policy “Dulmuluk” in the Independent Curriculum through P5 at SMALTI IGM Palembang - Delfiazi Puji Lestari; Feni Huspita Sari; Ade Uswatun Hasanah; Ida Utami Dwikurniawati; Rusdi Rusdi; Mumtaz Ibrahim (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2025)
This study examines the implementation of education policy based on local wisdom through the Merdeka Curriculum and the Project for Strengthening the Pancasila Student Profile (P5). In the context of globalization and rapid socio-cultural change, local cultural values are increasingly marginalized in formal education. Although the Merdeka Curriculum provides opportunities to integrate local wisdom through project-based learning, many schools still face challenges in translating this policy into practical educational activities. This study therefore focuses on how traditional Dulmuluk theater is integrated into school learning as a strategy for cultural preservation and character education. This research employed a qualitative descriptive approach to explore the dynamics of policy implementation within the school context. Data were collected through in-depth interviews, observation, and documentation involving school leaders, teachers implementing P5 activities, students, and cultural practitioners. The data were analyzed descriptively to identify patterns of implementation, supporting factors, and challenges in integrating local culture into educational practices. The findings show that the policy is implemented contextually by integrating Dulmuluk art into project-based learning activities. This approach encourages students to develop creativity, collaboration skills, and cultural awareness. The success of the program is supported by effective communication, institutional commitment from the school, and collaboration with cultural stakeholders. The study concludes that integrating local wisdom into educational policy implementation strengthens student character while also contributing to the preservation of regional cultural heritage.